Finite Element Analysis of Self-centering Moment Resistant Frames with and without Steel Plate Shear Wall. (2016) - Sreekumar, Anju; Asraff, A.K.; Ramanujan, Jayasree
Abstract: The Northridge earthquake on January 1994 damaged a large number of buildings all through Los Angeles. The most recurrent pattern of structural damage was the brittle failures at beam column junction in steel moment-resisting frames (MRF's)[6] This event brought out the need for further improving the Moment Resistant Frames and its connections. A new system of Moment Resisting Frames (MRF) commonly known as Self-Centering Moment Resisting Frames (SC-MRF) was developed. These designs are capable of resisting the seismic loads without sustaining much damage. The paper studies the behaviour of Self-Centering Moment Resisting Frames (SC-MRF) with and without steel plate shear walls subjected to cyclic loading. A detailed three dimensional finite element modeling using plate elements available in ANSYS FEA code is done. Geometric and material nonlinear stress analysis of the frame and a detailed comparison of the frame with and without steel plate shear walls is done. It can be observed that the sway of the SC-MRF frame is much higher than that of a conventional frame, but by introducing a thin steel plate shear wall this deformation can be brought down to a much lower value.